On new traveling wave solutions of the Hirota-Satsuma coupled KdV equation - Gencoglu, M. Tuncay; Akgul, Ali; İnç, Mustafa (Mustafa BAYRAM, 2017)
The improved (G? /G)-expansion method is applied to reach the different type soliton solitions of the Hirota-Satsuma Coupled KdV (HSCKdV) equation. It is obtained hyperbolic, triangular, periodic wave and kink soliton solitions of this equation. The method is an effective one to reach the different types of solutions of nonlinear partial differential equations and systems. Finally, the numerical simulations add to these obtained solutions.